Perumusan Blue Ocean Strategy dan Coopetition dalam Pengembangan Desa Wisata Menuju Pariwisata Berkelanjutan untuk Meningkatkan Ekonomi Lokal di Kabupaten Klaten (Jurnal Manajemen Pembangunan Daerah, 2026)
AbstractThe tourism sector has an important role in the economic development of a country. The tourism village is a strategy to increase tourism attractions by utilizing the cultural, environmental and village resource potential. In Klaten Regency, Ponggok Village has succeeded in developing tourism with the establishment of Tirta Mandiri BUMDes which manages natural potential in the form of water sources and other tourist objects. However, not all tourist villages achieve similar success. Therefore, the right strategy is needed, such as the Blue Ocean Strategy and cooperation strategy, in developing tourism villages towards sustainable tourism. In this study, a SWOT analysis was carried out to identify the potential, weaknesses, opportunities and threats of tourism villages in Klaten Regency. In addition, the application of the Blue Ocean Strategy and cooperation strategy are also discussed as steps in developing tourism villages. It is important to involve various related parties, such as the government, community, academics, and tourism industry players, as well as carry out periodic monitoring and evaluation to achieve sustainable tourism in Klaten Regency.Key words: Blue Ocean Strategy, Coopetition, Sustainable Tourism